Illegal vehicles modification: the needs to reform the delegations of enforcement power/ Amier Fitri Abdul Rahim…[et al.] - Abdul Rahim, Amier Fitri; Azmi, Khamarul Hazim; Suhaimi, Muhammad Syafiq; Mohd Halim, Nur Hafifah; Adnan, Siti Hazwani (Faculty of Law, 2010)
People usually modified their vehicles with the purpose to make their vehicles to have an outstanding feature. As a result, the vehicle modifications grew to the extent that, it becomes extreme modification. There are certain modifications which are allowed by the authority. However, most of the modification done nowadays is not approve by the authority because they find it is unsuitable and dangerous. This unapproved modification can be regarded as illegal modifications by the authority. The Road Transport Department has identified high number of cases regarding the illegal modified cars and motorcycles in Peninsular Malaysia, which have been compounded. ITic purpose of this research is to study the enforcement conducted by the authority relevant to this matter. This project paper is based on an analysis of the legal statutes on illegal vehicle modifications which have been used as an authority. Our research is concerning a legal study on the need to reform the jurisdiction to enforce the Guidelines of Illegal Vehicles Modifications in Malaysia. Road Transport Act 1987, together with Motor Vehicles (Construction and Use) Regulations 1959 will be analysed as a mechanism in solving illegal vehicle modifications in this country. Our project paper provides the recommendation to reform the jurisdiction to enforce the guidelines of illegal vehicles modifications in Malaysia.